Attachment to God, Contingent Self-Worth, and Mental Health Outcomes in U.S. Collegiate Athletes - Upenieks, Laura (Journal of religion and health, 2024)
Scholars and practitioners have recently devoted increased attention to the psychological well-being of student-athletes. However, sparse research has examined the role of religion/spirituality in well-being in athletic populations. In a sample of U.S. collegiate athletes (N = 415), the present study assessed how the divine relationship, measured by attachment style to God, associates with depressive and anxiety symptoms in a sample of collegiate student-athletes, as well as the mediating role of contingent self-worth based on the approval of others in this process. Results show that secure attachment to God is associated with fewer mental illness symptoms, whereas avoidant and anxious attachment to God are associated with greater mental illness symptoms. Contingent self-worth based on others’ approval partially mediates each of these associations. Implications for the religion and health literature and sport practitioners are discussed.